Archigetes Leuckart, 1878 (Cestoda, Caryophyllidea): diversity of enigmatic fish tapeworms with monoxenic life cycles - Uhrovič, Dalibor; Oros, Mikuláš; Kudlai, Olena; Kuchta, Roman; Scholz, Tomáš (Parasite (Paris, France), 2022)
The caryophyllidean genus Archigetes Leuckart, 1878 is unique among all tapeworms in that its species can mature in invertebrate hosts (Oligochaeta), i.e., have a monoxenic (direct) life cycle. All five species were described as progenetic plerocercoids in oligochaetes and two of them also as adults from cypriniform fishes. Two species, A. sieboldi Leuckart, 1878 and A. iowensis Calentine, 1962, were found in North America in non-native common carp (Cyprinus carpio). A molecular study of caryophyllideans from the southern United States has revealed the occurrence of three new species in native freshwater fishes (Catostomidae, Ictiobinae): Archigetes loculotruncatus n. sp. from Ictiobus bubalus, I. niger and Carpiodes cyprinus is the largest representative of the genus and differs by a loculotruncate scolex. Archigetes megacephalus n. sp. from Ictiobus niger, I. bubalus and I. cyprinellus is characterised by a prominent, bothrioloculodiscate scolex. Archigetes vadosus n. sp. from I. bubalus is typified by a globular scolex with very shallow loculi; it differs from the closely related A. sieboldi in the shape of the body, with a distinct neck region and a scolex wider than the remaining body. Archigetes iowensis Calentine, 1962 becomes a junior synonym of Paraglaridacris limnodrili (Yamaguti, 1934). The generic diagnosis of Archigetes is amended and a key to identification of North American taxa is provided. Species of Archigetes and Paraglaridacris differ from each other most conspicuously in the structure of the ovary, which is follicular in Archigetes versus compact in Paraglaridacris.
Keywords: Animals; Female; Eucestoda; Molecular prospecting; Cestoda; ženské pohlaví; Species diversity; lsrDNA; kapři; máloostní; Ictiobinae; stadia vývoje; Fish; Catostomidae; Histology; North America; Spojené státy americké; Severní Amerika; Comparative morphology; Carps; United States; Cypriniformes; Life Cycle Stages; zvířata; Nearctic Region; SEM